Enhanced plasma half-life and efficacy of engineered human albumin-fused GLP-1 despite enzymatic cleavage of its C-terminal end - Jeannette Nilsen; Kristin Hovden Aaen; Sopisa Benjakul; Fulgencio Ruso-Julve; Thomas Uwe Greiner; Daniela Bejan; Maria Stensland; Sachin Singh; Tilman Schlothauer; Inger Sandlie; Jan Terje Andersen (Communications Biology)
Abstract Albumin has a long plasma half-life due to engagement of the neonatal Fc receptor (FcRn), which prevents intracellular degradation. However, its C-terminal end can be cleaved by carboxypeptidase A, and removal of the last leucine residue (L585) weakens receptor binding, reducing its half-life from 20 days to 3.5 days in humans. This biology has so far been overlooked when designing human albumin-fused biologics. Thus, there is a need for an engineering strategy to secure favorable FcRn binding and pharmacokinetic properties. Here, we show that a branched aliphatic amino acid or methionine at position 585 of albumin is required for optimal receptor binding, which cannot be replaced to prevent enzymatic cleavage without negatively affecting FcRn engagement. As a solution, we report that C-terminally cleaved albumin can be efficiently rescued from intracellular degradation by introducing amino acid substitutions that improve FcRn binding. This albumin-engineering strategy was also effective when applied with a therapeutic fusion partner, glucagon-like peptide 1 (GLP-1), resulting in a 2-fold increase in plasma half-life and prolonged efficacy in human FcRn transgenic mice. We demonstrate how human albumin fusions should be tailored to ensure a long plasma half-life and enhanced efficacy of fused biologics, despite potential C-terminal cleavage in vivo.